Shaping entrepreneurial performance in small business sectors: does Islamic financial institutions’ support matter? - Yusfiarto, Rizaldi; Abdeljawad, Islam; Syarifah, Lailatis; Rosman, Romzie; Febriyanto, Ahmad; Ibrahim, Muhammad Hanif (World Scientific, 2025)
This study explores the role of Islamic financial institutions’ (IFIs) support in the entrepreneurial success of Muslim-owned micro, small and medium-sized enterprises (MSMEs). It also integrates the constructs of Islamic financial literacy, management control systems and the alleviation of financial constraints as key components of business internalization. The study involved 265 Muslim MSME owners, who were analyzed using partial least squares structural equation modeling (PLS-SEM). The empirical results reveal that IFIs play a significant role in enhancing entrepreneurial performance by enabling MSME actors to access both tangible and intangible resources critical to business success. Furthermore, the findings emphasize that IFIs act not only as capital providers but also as entrepreneurial support organizations, facilitating strategic guidance to support economic transformation through a more integrated approach grounded in Islamic values.